PERANCANGAN MEDIA PENGENALAN KESENIAN TRADISIONAL INDONESIA BERBASIS ONLINE PUBLIC ACCESS CATALOGUE (OPAC) - Erri wahyu Puspitarini; Mukhammad Fatkhu Rozi (STMIK YADIKA BANGIL, 2014)
The rapid development of the Internet spurred the growth of available data, which in turn requires the support of information technology to transform data into useful information. As well as the preservation of traditional arts in Indonesia. Rich variety of traditional arts which are categorized into several art forms require information technology in spreading knowledge of traditional art, so that the public get to know and help preserve the heritage of this beloved nation. Website to review many of the traditional arts in cyberspace, but the information provided in only one regional scope, and use the search facility on the website is still not up. Online Public Access Catalogue (OPAC) which is generally used by libraries to facilitate visitors in search of a book, this facility is implemented in the website contain information of a traditional Indonesian arts will facilitate users in finding data, and is used as a medium for artistic recognition traditionally. Keywords: Online Public Access Catalogue (OPAC), Kesenian Tradisional,Website